Poverty Reduction Support Credits : Lao PDR Country Study - Grawe, Roger (Washington, DC: World Bank, 2017)
The Lao PDR has been a one-party, socialist state since the overthrow of the monarchy by the communist Pathet Lao in 1975, which was preceded by a long period of civil and regional strife. After a decade of relative isolation and close military cooperation with Vietnam, the new economic mechanism, introduced in 1986, ushered in an era of market-based reforms, which has continued to the present day. Lao PDR is one of the poorest countries in East Asia, with a 2006 per capita income of US$ 500. In 2004, 71 percent of its population of 5.7 million lived on less than US$ 2/day and 23 percent on less than US$ 1/day. However Lao PDR has grown rapidly since the inauguration of reforms two decades ago. During the 1990s growth averaged 6 percent per annum despite severe imbalances during the Asian crisis. Following successful stabilization, growth continued to average close to 6 percent during 2001-2004, accelerating in 2005-2007 to over 7 percent. Inflation remained well below 10 percent since 2005. Although Lao PDR qualifies for the Heavily Indebted Poor Countries (HIPC) initiative, the Government has chosen to maintain normal creditor relations. The latest debt sustainability analysis confirms that, while risk of debt distress is high, medium term debt service is manageable, contingent on continued reform and prudent fiscal management. Foreign direct investment has almost quadrupled between 2004 and 2007, and exceeds US$ 800 million annually, mostly in hydropower and mining. Growth in Lao PDR has been pro-poor. Based on the national poverty line, the poverty headcount has fallen from almost half to one-third of the population during the decade ending in 2002-2003. The country's performance on other elements of poverty reduction as summarized in the millennium development goals is mixed.